Mental Health Stigma in the Military - Acosta, Joie D. (RAND Corporation, 2014)
This report assesses the U.S. military's approach to reducing stigma for mental health disorders and their treatment, how well it is working, and how it might be improved. It presents priorities for program and policy development and research and evaluation to get service members the treatment they need as efficiently and effectively as possible.